Avascular osteonecrosis of the premaxilla secondary to disseminated intravascular coagulation: a case report - Mouraret Alizée; Gérard Eric; Le Gall Joey; Curien Rémi (EDP Sciences, 2018)
Introduction: Disseminated intravascular coagulation (DIC) is a complexe systemic disorder characterized by a widespread activation of the coagulation, that may lead to thrombosis, ischemia and finally, end-organ failure. The clinical presentation of DIC depends on the site of intravascular coagulation and the severity of the disease process. Avascular osteonecrosis is a pathological state, that can occur secondary to DIC and where a reduced vascular supply leads to ischemia and bone necrosis. Observation: A 83 years old patient was sent to the oral surgery department for tooth mobility in the premaxilla, following the diagnosis of sepsis and DIC induced acute myeloid leukemia, one month ago. The examination showed an exposed avascular bone behind the 12-11-21. A diagnosis of DIC induced osteonecrosis of the premaxilla was made. A resection surgery was then programmed. Discussion: DIC may generates thrombi that might occlude intraosseous vessels in the premaxilla, and lead to bone necrosis. The maxilla is supplied by multiple branches of external carotide artery, therefore, usually, there is a lower risk of osteonecrosis in the maxilla. Nevertheless, since 1993, 4 cases of avascular necrosis of the maxilla secondary to DIC are repported in literature. Conclusion: This kind of complication, although being rare, can be dramatic for the patient as bone and aesthetic defects. Early support and management of these complications is necessary.